KESULITAN MAHASISWA DALAM PEMBUATAN VIDEO PEMBELAJARAN MENGGUNAKAN MICROSOFT POWERPOINT - Hera Deswita (Universitas Muhammadiyah Kotabumi, 2021)
Video has become one of the main learning tools in distance learning systems. Students as prospective teachers must be able to make quality and interesting videos. One easy-to-use application for creating videos is Microsoft powerpoint. The purpose of this study is to describe the difficulty of students in making learning videos using Microsoft PowerPoint. The research subject is a 5th semester student who took the learning media course on condition that he has passed computer courses I. The research instrument is a questionnaire. Data analysis techniques are qualitatively covering reduction, presenting data, verifying and checking back. Based on the analysis of data it can be concluded that the difficulty of students in making learning videos is that students still have less knowledge in operating Microsoft powerpoint, less creative in designing video displays, low explaining skills and students still have low computer specifications.